Neurocysticercosis an epidemiological survey in two small rural communities - Walter O. Arruda; Natal J. Camargo; Rosana C. Coelho (Arquivos de Neuro-Psiquiatria)
The authors describe the epidemiological findings related to human taeniasis and cysticercosis, and swine cysticercosis in two small rural communities, Postinho (P) and Tigre (T), of South Brazil. The prevalence of epilepsy was 2.04% (P) and 2.25% (T). The prevalence of neurocysticercosis was 0.47% (P) and 0.93% (T), and prevalence of swine cysticercosis was 12.8% (P) and 27.8% (T). Taenia sp. infestation wis detected in 4.3% (P) and 4.6% (T) of stool examinations. The hyperendemic human taeniasis and cysticercosis and swine cysticercosis seems to be related to poor hygienic habits of the population, and the free access to human excreta by the pigs.